Food content on children movies from 2013 to 2018: taking food processing into account - Paula M. Horta; Bárbara B. Machado; Liziane V. de Souza (Elsevier, 2021)
Objective: Movies and TV programs directed to children contain food information that can potentially negative influence their food consumption. The NOVA classification is a useful system for monitoring food informational environment. Therefore, this study aimed to evaluate food content on children movies using the NOVA classification. Methods: The 13 top box office children movies released from 2013 to 2018 were evaluated. Each food reference was classified as unprocessed or minimally processed, processed and ultra-processed food (UPF) and as positive, negative, and neutral message transmitted. Results: One hundred and ninety-eight (n = 198) scenes that contained 555 food references were included. The frequency of references to unprocessed and minimally processed foods (60.1%) was similar to references of UPF (59.1%). Fruit/vegetables and sweets represented 37.9% of food appearances each. Scenes containing fruit/vegetables conveyed more negative (62.5%) or neutral messages (49.3%) than positive (26.4%). UPF scenes contained more positive (70.9%) and negative content (75.0%) than neutral (37.3%). Regarding UPF subcategories, sweets scenes were more positive (49.1%) than neutral (22.4%) and fast food meals scenes were more negative (37.5%) than neutral (5.9%). Conclusions: UPF, unprocessed food, and minimally processed foods have similar frequency in the movies. Except for fast food meals, UPF were commonly more associated with positive situations and unprocessed and minimally processed foods were more commonly associated with negative contexts.